Transformasi Etika Berbahasa di Kalangan Mahasiswa: Dampak Penggunaan Bahasa Gaul di Media Sosial - Hasbiah, Sitti (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
Social media platforms such as Instagram and TikTok have become the primary mediums for the spread of slang among university students. Slang, characterized by its informal and expressive nature, is now commonly used not only in daily interactions but also increasingly in academic settings. This study aims to determine the extent of Instagram and TikTok’s role in the dissemination of slang and its impact on the language etiquette of students at Universitas Brawijaya. A quantitative survey method was used with 40 respondents from various faculties. The findings reveal that most students are aware of the need to distinguish their language style between social media and academic forums. While slang is perceived as a form of expression and linguistic creativity, excessive use can reduce politeness and respect in formal communication. Therefore, stronger awareness and language literacy are needed so that students can use language contextually and ethically.